Prenatal genetic diagnosis - Milunsky, Aubrey (Henry Stewart Talks, 2023)
Prenatal genetic diagnosis, Prenatal imaging, Indications for prenatal genetic diagnosis, Genetic tests, Genetic laboratory evaluation, Microarray, Prenatal chromosomal microarray, Next generation sequencing, Whole exome sequencing, Whole genome sequencing, Preimplantation genetic testing